Islamic Social Reporting Factors For The Indonesian Islamic Commercial Banks - Budi Sukardi; Widiatmini Widiatmini; Fachrurazi Fachrurazi (LPPM ISNJ Bengkalis, 2022)
Islamic social reporting as part of the responsibility of Islamic banks in fulfilling Islamic social performance reporting can also be a priority for investors in making investment decisions. The use of the Islamic social reporting Index in the disclosure of company reports aims to fulfill investors' spiritual desires in the form of accountability to Allah. This study aims to determine the effect of firm age, firm size, and profitability on Islamic social reporting disclosure in Indonesian commercial banks. The study used quantitative methods, and the research population used the financial statements of 11 Indonesian Islamic commercial banks registered with the financial services authority (OJK) from 2014 to 2019. The research sample used 5 Indonesian Islamic commercial banks registered with the OJK and published from 2014 to 2019, using a purposive sampling technique. The data analysis technique with panel data was processed using EViews 10. The results showed that company age significantly affected Islamic social reporting disclosures; company size and profitability did not affect Islamic social reporting disclosures. The research has practical implications and contributes to the fulfillment of investor confidence and the accountability of Islamic companies to stakeholders to manage public fund investments according to sharia principles and sharia compliance standards.